Evaluating the performance of ASHA workers in rural and tribal areas in Kurnool division of Kurnool district, Andhra Pradesh - Biyyala, Renuka; Moola, Ram Sagar Reddy; Arepalli, Sreedevi (International Journal Of Community Medicine And Public Health, 2019)
Background: ASHA is a health activist in the communities who creates awareness on health and its social determinants and mobilizes the community towards local health planning and increased utilization and accountability of the existing health services. This study was conducted with the aim of evaluating the work performance of ASHAs in tribal and remote rural areas in Kurnool division of Kurnool district. Methods: This is a community based observational and cross sectional study carried out from July 2014 to July 2015. Six PHCs of Atmakur CHNC namely Kottalcheruvu, Bairluty, Kothapally, Yerramattam, Gokavaram, Pamulapadu were selected for the study by using multistage random sampling technique. 65 ASHAs from 20 SCs of these six PHCs had participated in the study for evaluation of their performance in the field. Results: Majority of ASHAs had average level of the performance in counselling of antenatal cases, escorting postnatal cases, motivating cases for family planning adoption, escorting family planning cases whereas the performance level was found to be good among majority of ASHAs with regard to escorting antenatal cases, counselling of postnatal cases and getting children immunized. Majority of ASHAs were not performing activities regarding creating awareness on social determinants of health, providing primary medical care for minor ailments, informing births and deaths to SC/PHC, distributing ORS, IFA and chloroquine. Conclusions: Regular on job training as well as review training for ASHAs every 6 months helps them to increase their participation in various activities with a rejuvenated enthusiasm. The incentives for ASHA must be raised and paid promptly to them to improve their performance.